Implementasi Pengamanan Protokol MAVLink menggunakan Algoritma Kriptografi SIMECK - Ahmad Faiz; Ari Kusyanti; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
MAVLink stands for Micro Air Vehicle Link which is an unmanned system lightweight message serialization protocol. This protocol is commonly used in autopilot systems, especially ArduPilot and PX4 and provides advanced features not only for monitoring and controlling the mission of unmanned systems but also for integration into the Internet. Since the MAVLink protocol is carried over wireless channels, this makes it vulnerable. against attack-based and also the lack of support in terms of security procedures both in secrecy and the authentication mechanism is not supported natively. This causes the MAVLink protocol to be easily hacked. Therefore, to reduce the security risk, it is necessary to secure the communication protocol between the UAV to the GCS by using the SIMECK algorithm. SIMECK algorithm is a combination of encryption and decryption algorithm between SIMON algorithm and SPECK algorithm. Users can use the SIMECK cipher by considering the software and hardware needed without disturbing the performance of the security system. The purpose of the SIMECK algorithm is to provide security in data transmission and also performance flexibility to be used for developers. The implementation of the SIMECK algorithm on this system makes it resistant to passive attacks and even active attacks.